Implementing Entrepreneurship Practice and Networks Building Through Collaboration at Bussiness Festival Event at Darunnajah University - Farah Diba (Future Science, 2023)
Entrepreneurship education at a university degree does not only provide information theoretically but also is expected to apply a mature mindset to students practically in terms of growing their interest in entrepreneurship. Networks are one of the important factors in entrepreneurship. SMEs itself develop networks through several components, including collaborations. This is what Jakpreneur did through their support for the Business Festival event (BUFEST) at Darunnajah University. This research uses a qualitative approach with an explanatory research design which aims to explore the reasons of provincial government and Jakpreneur in expanding their network through support in this event. This research found that BUFEST event as a university bridge to accommodate students practically. Moreover, increasing students' motivation to begin entrepreneurship. Otherwise, Jakpreneur Association could expand their organizational network through the event, such as recruiting bazaar participants to join as Jakpreneur members and offering ideas and opportunities to students for opening franchises of their business. The limitation model could be solved by joint business, students will learn how to begin business in teamwork. The main conclusion of implementation entrepreneurship practice is a marketplace opportunity. Students will get benefits by joining the member of the association due to the limitation of renting a location to open entrepreneurship. They can practice entrepreneurship by joining bazaar to bazaar provided